Method for converting perovskite crystal morphology in titanium-containing blast furnace slag into spheroidic morphology

By adding CaO, high titanium slag and CaTiO3 to the titanium-containing blast furnace slag and modifying it at a high temperature of 1500°C, the perovskite crystals are transformed from dendritic to spherical, which solves the problem of low titanium recovery and achieves a significant improvement in titanium recovery.

CN119565760AInactive Publication Date: 2025-03-07HUAIAN COLLEGE OF INFORMATION TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411679031.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the perovskite crystal morphology of the titanium-containing blast furnace slag is dendritic, resulting in low dissociation of the monomer during subsequent grinding, thereby reducing the titanium recovery rate.

Method used

By adding CaO, high titanium slag and CaTiO3 to the titanium-containing blast furnace slag and modifying it at a high temperature of 1500°C, the perovskite crystals are transformed from dendritic to spherical, thereby improving the dissociation of the monomer.

Benefits of technology

This method significantly improves the monomer dissociation degree of perovskite crystals, thereby greatly improving the titanium recovery rate during ore dressing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565760A_ABST
    Figure CN119565760A_ABST
Patent Text Reader

Abstract

The invention discloses a method for converting perovskite crystal morphology in titanium-containing blast furnace slag into spheroidic morphology, which comprises the following steps: (1) primary modification: heating titanium-containing blast furnace slag, CaO, high titanium slag and CaTiO3 to 1500 + / -10 DEG C for modification to obtain primary modified slag; (2) primary reselection: crushing and grinding the primary modified slag to be below a 200 + / -10-mesh sieve, and carrying out primary reselection to obtain primary perovskite concentrate and tailings; (3) modifying the titanium-containing blast furnace slag and the primary perovskite concentrate to obtain secondary modified slag; and (4) crushing and grinding the secondary modified slag to below 200 + / -10 meshes, and carrying out secondary gravity separation to obtain secondary perovskite concentrate and tailings. CaO, high titanium slag and CaTiO3 are added into the titanium-containing blast furnace slag to improve the nucleation rate of perovskite crystals separated out from the titanium-containing blast furnace slag and increase the viscosity of the slag, so that the perovskite crystals are converted from a dendritic state to a spheroidal state, the monomer dissociation degree of the perovskite crystals in the subsequent ore grinding process is improved, and the titanium recovery rate in the ore dressing process is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallurgy, and in particular relates to a method for transforming the morphology of perovskite crystals in titanium-containing blast furnace slag into a quasi-spherical shape. Background Art

[0002] At present, the vanadium-titanium magnetite blast furnace ironmaking-converter vanadium extraction-steelmaking process is dominant. Panzhihua Iron and Steel Company, Chengde Iron and Steel Company and Russia's Chusov Steel Company adopt this process. After blast furnace ironmaking, most of the titanium components enter the slag phase to form titanium-containing blast furnace slag with a TiO2 content of 10~25%. China emits more than 3 million tons of titanium-containing blast furnace slag each year, and the cumulative emissions exceed 100 million tons. At present, titanium-containing blast furnace slag can only be piled up in slag yards, occupying a large amount of land and causing a waste of titanium resources. Therefore, realizing the comprehensive utilization of titanium-containing blast furnace slag is a key issue that needs to be urgently solved in the metallurgical field. In order to realize the comprehensive utilization of titanium-containing blast furnace slag, metallurgists have conducted a lot of research, and the products obtained by various research methods are used as classification standards, mainly including the following: (1) Preparation of building materials: Titanium-containing blast furnace slag is used in the production of building materials, such as cement and concrete.

[0003] (2) Preparation of photocatalytic materials: Perovskite has certain photocatalytic activity, and the main titanium-containing phase of titanium-containing blast furnace slag is perovskite. Therefore, titanium-containing blast furnace slag can be used to degrade wastewater such as methyl blue and phenol.

[0004] (3) Preparation of titanium-silicon alloy: Direct preparation of titanium-silicon alloy using titanium-containing blast furnace slag is one of the comprehensive utilization methods of titanium-containing blast furnace slag. This process can directly transform the titanium component in the slag into valuable products.

[0005] (4) Preparation of titanium dioxide: There are two methods for preparing titanium dioxide using titanium-containing blast furnace slag as raw material, one is the sulfuric acid method and the other is the alkali molten salt method.

[0006] (5) Preparation of titanium-rich material: Based on the principle that titanium oxide does not react with dilute hydrochloric acid, dilute hydrochloric acid is used to leach the alkaline oxides in the titanium-containing blast furnace slag, thereby increasing the TiO2 content in the slag and obtaining titanium-rich material.

[0007] (6) Preparation of titanium carbide or titanium carbonitride: In a H2 atmosphere, the product of carbon thermal reduction of titanium-containing blast furnace slag is titanium carbide; in a N2 atmosphere, the product is titanium carbonitride.

[0008] Preparation of building materials is a method of comprehensive utilization of titanium-containing blast furnace slag, but this method does not recover the titanium component in the titanium-containing blast furnace slag, resulting in a waste of titanium resources; using titanium-containing blast furnace slag as a photocatalytic material is a high value-added comprehensive utilization method, but the photocatalytic performance of titanium-containing blast furnace slag is relatively weak; using titanium-containing blast furnace slag as a raw material to produce titanium silicon alloy, this method can achieve the comprehensive utilization of titanium-containing blast furnace slag, but the application range of the alloy is narrow and the amount used is small; since the total content of impurity elements in titanium-containing blast furnace slag exceeds 70%, the method of preparing titanium dioxide by leaching titanium-containing blast furnace slag with concentrated sulfuric acid has a large acid consumption and produces a large amount of waste acid and waste slag, which is serious. Severe environmental pollution; the alkali consumption of preparing titanium dioxide by alkali molten salt method is large, and the cost of recovering sodium salt is high. In addition, treating titanium-containing blast furnace slag with alkali at high temperature will cause serious environmental pollution; using dilute hydrochloric acid to leach the alkaline oxides in the titanium-containing blast furnace slag to obtain titanium-rich materials, this method has a long acid leaching time, consumes a lot of hydrochloric acid, and produces a large amount of waste acid and waste slag; the titanium-containing blast furnace slag is carbonized at high temperature to enrich the titanium component in titanium carbide or titanium carbonitride. The average diameter of these crystals is only a few microns, resulting in a low degree of dissociation in subsequent grinding. In addition, the key problem of high carbonization power consumption has not been solved, and the electricity cost accounts for 70-80% of the total cost. In summary, although the above methods can achieve the comprehensive utilization of titanium-containing blast furnace slag, they all have certain limitations, which restrict the industrial application of the above methods.

[0009] In order to overcome the limitations of the above methods and realize the comprehensive utilization of titanium-containing blast furnace slag, Sui Zhitong and others from Northeastern University proposed the "selective precipitation technology". The basic idea of ​​this technology is: (1) Create suitable physical and chemical conditions to promote the valuable elements dispersed in various mineral phases to be selectively transferred and enriched in the designed mineral phase under the drive of chemical potential gradient, thus completing "selective enrichment"; (2) Reasonably control relevant factors to promote the "selective precipitation and growth" of the enriched phase; (3) Grind and sort the modified slag (the slag obtained by perovskite modification of titanium-containing blast furnace slag, the same below) to complete the "selective separation" of the enriched phase, and the obtained enriched phase is an artificial rich ore rich in the elements to be extracted.

[0010] Based on the basic idea of ​​"selective precipitation technology", Sui Zhitong and others selected perovskite as the enriched phase, conducted a large number of experimental studies, and finally formed a process route of "selective precipitation technology to recover titanium components from titanium-containing blast furnace slag". This technology is to modify the molten titanium-containing blast furnace slag without additional heating. The additives used are conventional reagents or steel slag, so the production cost of this technology is low. In addition, the separated perovskite can be used as a raw material for titanium extraction, and the tailings (TiO2 content less than 10%) can be used to produce slag cement, truly realizing the comprehensive utilization of titanium-containing blast furnace slag. This technology optimizes the nucleation and growth conditions of perovskite by controlling the cooling rate and adding appropriate types and quantities of additives, so that the perovskite crystals are as coarse as possible to increase the particle size of the perovskite crystals, thereby improving the monomer dissociation degree in the subsequent grinding process. However, the effect of perovskite crystal morphology on the monomer dissociation degree during the grinding process has been ignored. Since perovskite crystallizes in a dendritic form, the perovskite is closely combined with the gangue phase, resulting in a low monomer dissociation degree of perovskite during the subsequent grinding process, thereby reducing the titanium recovery rate in subsequent gravity separation, flotation and other mineral processing processes. In summary, the fundamental reason for limiting the industrial application of "selective precipitation technology" is that perovskite precipitates in a dendritic form. Therefore, the present invention proposes a method for controlling the transformation of the perovskite crystal morphology from dendritic to spherical in titanium-containing blast furnace slag. This transformation can increase the monomer dissociation degree of perovskite during grinding, thereby greatly improving the recovery rate of subsequent perovskite mineral processing (such as gravity separation, flotation, etc.). Summary of the invention

[0011] In view of the problems existing in the prior art, the present invention proposes a method for transforming the morphology of perovskite crystals in titanium-containing blast furnace slag into a quasi-spherical shape, wherein CaO, high-titanium slag and CaTiO3 are added to the titanium-containing blast furnace slag to increase the nucleation rate of perovskite crystals precipitated from the titanium-containing blast furnace slag and increase the viscosity of the slag, so that the perovskite crystals are transformed from dendritic to quasi-spherical, thereby improving the monomer dissociation degree of the perovskite crystals in the subsequent grinding process, and further increasing the titanium recovery rate in the ore dressing process.

[0012] The technical solution adopted by the present invention is: a method for transforming the morphology of perovskite crystals in titanium-containing blast furnace slag into a spherical shape, comprising the following steps: (1) Primary modification: Titanium-containing blast furnace slag, high titanium slag with CaO and TiO2 content greater than 90wt%, and CaTiO3 are heated to 1500±10℃. The purpose of selecting a high temperature of 1500℃ for modification is that at 1500℃, all of the above solid raw materials can be converted into liquid state, and then air can be sprayed into the slag for oxidation. This temperature ensures that all solid raw materials are converted into liquid state.

[0013] The amount of CaO added is 15-25wt% of the mass of the titanium-containing blast furnace slag, the amount of high titanium slag added is 20-30wt% of the mass of the titanium-containing blast furnace slag, and the amount of CaTiO3 added is 2-10wt% of the mass of the titanium-containing blast furnace slag. After heat preservation, air is sprayed into the slag, and the temperature begins to drop after the spraying is completed. The temperature is cooled to room temperature to obtain a primary modified slag. (2) Primary gravity separation: crush the primary modified slag and grind it to 200±10 mesh, and then perform a gravity separation to obtain primary perovskite concentrate and tailings; (3) Secondary modification: heating the titanium-containing blast furnace slag and the primary perovskite concentrate to 1500±10°C, wherein the primary perovskite concentrate is added in an amount of 40-60% of the mass of the titanium-containing blast furnace slag; after heat preservation, blowing air into the slag; after the blowing is completed, cooling begins; the temperature is cooled to room temperature to obtain secondary modified slag; (4) Secondary gravity separation: The secondary modified slag is crushed and ground to a size below 200±10 mesh, and then subjected to secondary gravity separation to obtain secondary perovskite concentrate and tailings; (5) End or repeat steps (3) and (4).

[0014] On the basis of the above scheme, preferably, the titanium-containing blast furnace slag is condensed titanium-containing blast furnace slag or molten titanium-containing blast furnace slag.

[0015] Based on the above scheme, as a preferred embodiment, in step (1), the insulation time is 60±10 minutes, and the blowing time is 5-15 minutes; In step (3), the insulation time is 60±10 minutes, and the injection time is 2-8 minutes. The purpose of limiting the insulation and injection time is to ensure that the low-valent titanium oxides in the titanium-containing blast furnace slag and high-titanium slag are converted into tetravalent titanium oxides.

[0016] Based on the above scheme, preferably, in step (1) and step (3), the air flow rate is 4±1 L / min. The purpose of adopting this flow rate limitation is to ensure that sufficient air is provided, thereby converting low-valent titanium oxides in titanium-containing blast furnace slag and high-titanium slag into tetravalent titanium oxides.

[0017] On the basis of the above scheme, as a preference, in step (1) and step (3), the heating rate and cooling rate are both 5±1°C / min. The purpose of adopting this rate limit is: because the heating rate has no effect on the test, there is no specific requirement for the heating rate. However, the cooling rate should be controlled at about 5°C / min. The cooling rate can be faster, but not slower. If it is too slow, for example 1°C / min, it will cause the perovskite to precipitate in a dendritic form. In other words, a slow cooling rate is conducive to the precipitation of perovskite in a dendritic form, and a fast cooling rate is conducive to the precipitation of perovskite in a spherical form.

[0018] On the basis of the above scheme, as a preferred embodiment, the first re-selection and the second re-selection are shaking table re-selection.

[0019] The principle of the present invention is that by adding CaO to titanium-containing blast furnace slag, the effect is that at high temperature, CaO reacts with TiO2 (obtained by blowing air oxidation) to generate CaTiO3 (perovskite), thereby increasing the concentration of perovskite in the slag, thereby increasing the nucleation rate of CaTiO3 and promoting the transformation of perovskite from dendritic to spherical.

[0020] The purpose of adding high-titanium slag is: because the titanium oxides contained in high-titanium slag are mainly low-valent titanium oxides, the purpose of adding high-titanium slag is to provide low-valent titanium oxides, which are then oxidized to obtain TiO2. TiO2 reacts with CaO to generate CaTiO3, thereby increasing the concentration of perovskite in the slag, thereby increasing the nucleation rate of CaTiO3, and promoting the transformation of perovskite from dendritic to spherical.

[0021] The functions of adding CaTiO3 are: first, to be used as a nucleating agent to increase the nucleation rate and realize the transformation of CaTiO3 from dendritic to spherical; second, to increase the CaTiO3 concentration in titanium-containing blast furnace slag, thereby increasing the nucleation rate of CaTiO3 and realizing the transformation of CaTiO3 from dendritic to spherical; third, to increase the viscosity of titanium-containing blast furnace slag, because the melting point of CaTiO3 is as high as 1975°C. After addition, CaTiO3 exists in the form of solid particles, thereby reducing the diffusion rate of the solute, resulting in a significant decrease in the three growth rates of the perovskite crystals in the three-dimensional directions, and at the same time reducing the difference in the three growth rates in the three-dimensional directions, making the three growth rates tend to be the same, causing the perovskite crystals to precipitate in a spherical shape.

[0022] The low-valent titanium oxides in high-titanium slag are oxidized into tetravalent titanium oxide (TiO2) at high temperature, and then TiO2 reacts with CaO to form CaTiO3. The interaction between the two additives, high-titanium slag and CaO, is used to increase the concentration of CaTiO3, thereby increasing the nucleation rate of CaTiO3 and promoting the transformation of perovskite from dendritic to spherical.

[0023] First, use a jaw crusher to crush the modified slag to about 2 mm, then grind it with a rod mill for 5 minutes, take out the modified slag powder, sieve it with a 200-mesh sieve, continue to grind the modified slag powder that does not pass the 200-mesh sieve with a rod mill for 5 minutes, then take out the modified slag powder, sieve it with a 200-mesh sieve, and repeat the above process.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) By controlling the transformation of the perovskite crystal morphology from dendritic to spherical in titanium-containing blast furnace slag, the monomer dissociation degree of perovskite in the subsequent grinding process can be improved, thereby greatly increasing the titanium recovery rate in the mineral processing process.

[0025] (2) In the present invention, only the first furnace needs to purchase additives such as CaO, high-titanium slag and CaTiO3. Starting from the second furnace test, gravity separation concentrate is used as an additive, which greatly saves production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a flow chart of the present invention; Figure 2 This is a metallographic photograph of the raw material titanium-containing blast furnace slag; Figure 3 is a metallographic photograph of a furnace of modified slag in Example 1; Figure 4 is a metallographic photograph of the modified slag from the second furnace in Example 1; Figure 5 is a metallographic photograph of a furnace of modified slag in Example 2; Figure 6 is a metallographic photograph of the modified slag from the second furnace in Example 2; Figure 7 is a metallographic photograph of a furnace of modified slag in Example 3; Figure 8 This is a metallographic photograph of the modified slag from the second furnace in Example 3. DETAILED DESCRIPTION

[0027] The present invention will be further described below by way of examples, but the scope of the present invention is not limited thereto.

[0028] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0029] The composition of titanium-containing blast furnace slag is: Table 1 Main chemical components of titanium-containing blast furnace slag (%, mass fraction) CaO <![CDATA[SiO2]]> <![CDATA[TiO2]]> <![CDATA[Al2O3]]> MgO <![CDATA[Fe2O3]]> MnO other 28.60 26.11 16.10 13.57 6.93 4.85 0.82 3.02 Example

[0030] Titanium-containing blast furnace slag, CaO, high titanium slag (TiO2 content greater than 90wt%), and CaTiO3 are heated to 1500℃, wherein the amount of CaO added is 21wt% of the mass of the titanium-containing blast furnace slag, the amount of high titanium slag added is 30wt% of the mass of the titanium-containing blast furnace slag, and the amount of CaTiO3 added is 5wt% of the mass of the titanium-containing blast furnace slag. The mixture is kept warm for 60 min, and then air is blown into the slag for 15 min. After the blowing is completed, the temperature is lowered to room temperature. The cooled slag (a furnace of modified slag) is crushed and ground to a size below 200 mesh, and a shaking table gravity separation (one gravity separation) is performed to obtain concentrate and tailings. The titanium-containing blast furnace slag and the gravity separation concentrate are heated to 1500℃, wherein the amount of concentrate added is 50% of the mass of the titanium-containing blast furnace slag. The mixture is kept warm for 60 min, and then air is blown into the slag for 5 min, and then the temperature starts to drop after the injection is completed, and the temperature is cooled to room temperature; the cooled slag (modified slag from the second furnace) is crushed and ground to a size below 200 mesh, and then re-selected (secondary re-selection) is performed to obtain concentrate and tailings.

[0031] The TiO2 content of the primary gravity concentrate is 51wt%, and the titanium recovery rate is 65%; the TiO2 content of the secondary gravity concentrate is 50wt%, and the titanium recovery rate is 63%. Figure 3 , 4 shown. Example

[0032] Titanium-containing blast furnace slag, CaO, high titanium slag (TiO2 content greater than 90wt%), and CaTiO3 are heated to 1500℃, wherein the amount of CaO added is 21wt% of the mass of the titanium-containing blast furnace slag, the amount of high titanium slag added is 30wt% of the mass of the titanium-containing blast furnace slag, and the amount of CaTiO3 added is 8wt% of the mass of the titanium-containing blast furnace slag. The temperature is kept for 60 minutes, and then air is sprayed into the slag for 15 minutes. After the spraying is completed, the temperature begins to drop and the temperature is cooled to room temperature; the cooled slag (modified slag from the first furnace) is crushed and ground to a 200-mesh sieve, and gravity separation (secondary gravity separation) is carried out to obtain concentrate and tailings; the titanium-containing blast furnace slag and the gravity separation concentrate are heated to 1500℃, wherein the amount of concentrate added is 50% of the mass of the titanium-containing blast furnace slag, and the temperature is kept for 60 minutes. min, and then air is blown into the slag for 5 min. After the blowing is completed, the temperature begins to drop to room temperature. The cooled slag (modified slag from the second furnace) is crushed and ground to a 200-mesh sieve, and gravity separation (secondary gravity separation) is carried out to obtain concentrate and tailings.

[0033] The TiO2 content of the primary gravity concentrate is 51wt%, and the titanium recovery rate is 64%; the TiO2 content of the secondary gravity concentrate is 52wt%, and the titanium recovery rate is 67%. Figure 5 , 6 shown. Example

[0034] Titanium-containing blast furnace slag, CaO, high titanium slag (TiO2 content greater than 90wt%), and CaTiO3 are heated to 1500℃, wherein the amount of CaO added is 18wt% of the mass of the titanium-containing blast furnace slag, the amount of high titanium slag added is 25wt% of the mass of the titanium-containing blast furnace slag, and the amount of CaTiO3 added is 8wt% of the mass of the titanium-containing blast furnace slag. The temperature is kept for 60 minutes, and then air is sprayed into the slag for 10 minutes. After the spraying is completed, the temperature begins to drop and the temperature is cooled to room temperature; the cooled slag (a furnace of modified slag) is crushed and ground to a 200-mesh sieve, and gravity separation (one gravity separation) is carried out to obtain concentrate and tailings; the titanium-containing blast furnace slag and the gravity separation concentrate are heated to 1500℃, wherein the amount of concentrate added is 50% of the mass of the titanium-containing blast furnace slag, and the temperature is kept for 60 minutes. min, and then air is blown into the slag for 5 min. After the blowing is completed, the temperature begins to drop to room temperature. The cooled slag (modified slag from the second furnace) is crushed and ground to a 200-mesh sieve, and gravity separation (secondary gravity separation) is carried out to obtain concentrate and tailings.

[0035] The TiO2 content of the primary gravity concentrate is 48wt%, and the titanium recovery rate is 64%; the TiO2 content of the secondary gravity concentrate is 50wt%, and the titanium recovery rate is 66%. Figure 7 , 8 shown.

[0036] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A method for transforming the morphology of perovskite crystals in titanium-containing blast furnace slag into a quasi-spherical shape, characterized in that: The following steps are involved: (1) Primary modification: heating titanium-containing blast furnace slag, CaO, high titanium slag with a TiO2 content greater than 90wt%, and CaTiO3 to 1500±10°C, wherein the amount of CaO added is 15-25wt% of the mass of the titanium-containing blast furnace slag, the amount of high titanium slag added is 20-30wt% of the mass of the titanium-containing blast furnace slag, and the amount of CaTiO3 added is 2-10wt% of the mass of the titanium-containing blast furnace slag; after heat preservation, air is sprayed into the slag, and the temperature is cooled down after the spraying is completed, and the temperature is cooled to room temperature to obtain primary modified slag; (2) Primary gravity separation: crush the primary modified slag and grind it to 200±10 mesh, and then perform a gravity separation to obtain primary perovskite concentrate and tailings; (3) Secondary modification: heating the titanium-containing blast furnace slag and the primary perovskite concentrate to 1500°C, wherein the primary perovskite concentrate is added in an amount of 40-60% of the mass of the titanium-containing blast furnace slag; after heat preservation, blowing air into the slag; after the blowing is completed, cooling begins; the temperature is cooled to room temperature to obtain secondary modified slag; (4) Secondary gravity separation: The secondary modified slag is crushed and ground to a size below 200±10 mesh, and then subjected to secondary gravity separation to obtain secondary perovskite concentrate and tailings; (5) End or repeat steps (3) and (4).

2. The method for controlling the transformation of the perovskite crystal morphology from dendritic to spherical in titanium-containing blast furnace slag according to claim 1, characterized in that: The titanium-containing blast furnace slag is condensed titanium-containing blast furnace slag or molten titanium-containing blast furnace slag.

3. The method for controlling the transformation of the perovskite crystal morphology from dendritic to spherical in titanium-containing blast furnace slag according to claim 1, characterized in that: In step (1), the insulation time is 60±10 minutes, and the blowing time is 5-15 minutes; In step (3), the insulation time is 60±10 min, and the blowing time is 2~8 min.

4. The method for controlling the transformation of the perovskite crystal morphology from dendritic to spherical in titanium-containing blast furnace slag according to claim 3, characterized in that: In step (1) and step (3), the air flow rate is 4±1 L / min.

5. The method for controlling the transformation of the perovskite crystal morphology from dendritic to spherical in titanium-containing blast furnace slag according to claim 1, characterized in that: In step (1) and step (3), the heating rate and cooling rate are both 5±1°C / min.

6. The method for controlling the transformation of the perovskite crystal morphology from dendritic to spherical in titanium-containing blast furnace slag according to claim 1, characterized in that: The first and second re-selection are shaker re-selection.